2003
DOI: 10.1104/pp.011676
|View full text |Cite
|
Sign up to set email alerts
|

The Sucrose TransporterStSUT1Localizes to Sieve Elements in Potato Tuber Phloem and Influences Tuber Physiology and Development,

Abstract: The sucrose (Suc) H-cotransporter StSUT1 from potato (Solanum tuberosum), which is essential for long-distance transport of Suc and assumed to play a role in phloem loading in mature leaves, was found to be expressed in sink tubers. To answer the question of whether SUT1 serves a function in phloem unloading in tubers, the promoter was fused to gusA and expression was analyzed in transgenic potato. SUT1 expression was unexpectedly detected not in tuber parenchyma but in the phloem of sink tubers. Immunolocaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 57 publications
4
99
1
1
Order By: Relevance
“…The unloading route may differ according not only to sink types, but also to sink development, sink function, and even to growth conditions for a particular sink type, and alternative unloading pathways may exist in the sinks with symplasmically interconnecting phloem (Patrick, 1997;Roberts et al, 1997;Oparka and Turgeon, 1999;Viola et al, 2001). These observations are supported by recent research revealing that the plasmodesmal conductivity can be programmatically reduced (Baluska et al, 2001;Itaya et al, 2002) and that the transgenic expression of both apoplasmic invertase (Sonnewald et al, 1997) and sugar transporter (Harrison, 1996;Kuhn et al, 2003) may occur in tissues characterized by a predominant symplasmic phloem pathway. Because of the probable limitations due to transmembrane solute movement, apoplasmic phloem unloading is theoretically scarcely realizable in strong sinks such as meristems, seeds, and fruits (Offler and Patrick, 1993;Wang et al, 1995b).…”
supporting
confidence: 70%
“…The unloading route may differ according not only to sink types, but also to sink development, sink function, and even to growth conditions for a particular sink type, and alternative unloading pathways may exist in the sinks with symplasmically interconnecting phloem (Patrick, 1997;Roberts et al, 1997;Oparka and Turgeon, 1999;Viola et al, 2001). These observations are supported by recent research revealing that the plasmodesmal conductivity can be programmatically reduced (Baluska et al, 2001;Itaya et al, 2002) and that the transgenic expression of both apoplasmic invertase (Sonnewald et al, 1997) and sugar transporter (Harrison, 1996;Kuhn et al, 2003) may occur in tissues characterized by a predominant symplasmic phloem pathway. Because of the probable limitations due to transmembrane solute movement, apoplasmic phloem unloading is theoretically scarcely realizable in strong sinks such as meristems, seeds, and fruits (Offler and Patrick, 1993;Wang et al, 1995b).…”
supporting
confidence: 70%
“…This reveals the dual function of PsSUT1, which is able to mediate both sucrose unloading and phloem loading. Indeed, many studies have found that SUT1 is expressed in both sink tissues and source tissues, and these carrier proteins are thought to play dual functions: regulating the loading in source tissues and unloading in sink tissues of photoassimilates (mainly sucrose) in apoplastic phloem transmembrane pathway (Lalonde et al, 1999;Kühn et al, 2003). For example, StSUT1 of Solanum tuberosum, which is responsible for assimilation loading, also plays an important role in tuber phloem unloading (Kühn et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies have found that SUT1 is expressed in both sink tissues and source tissues, and these carrier proteins are thought to play dual functions: regulating the loading in source tissues and unloading in sink tissues of photoassimilates (mainly sucrose) in apoplastic phloem transmembrane pathway (Lalonde et al, 1999;Kühn et al, 2003). For example, StSUT1 of Solanum tuberosum, which is responsible for assimilation loading, also plays an important role in tuber phloem unloading (Kühn et al, 2003). SUT genes cloned from Galega officinalis (Li et al, 2011), Malus pumila (Peng et al, 2011), Triticum aestivum (Deol et al, 2013), and Leymus chinensis (Su et al, 2013) are expressed both in source leaves and sink tissues such as seeds, fruits, and stems.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated fusion protein exhibited no discernible FRET, suggesting that protein stability may have been compromised. We have previously observed that within a binding protein family, only a subset may be facilely converted to working FRET sensors by simple linear fusion of chromophore variants 3 ; putative nanosensors may fail to show detectable FRET or show FRET but no ligand-dependent FRET change. SmAglE was fused in a similar manner but provided a FLIP with an extremely low starting ratio of ϳ0.7 and a sucrose-induced ratio change of only 0.05 (data not shown).…”
Section: Determining the Ligand Binding Specificity Of A Putativementioning
confidence: 99%
“…Even though much has been discovered about phloem import of sucrose, essentially nothing is known about the export from photosynthetic mesophyll cells. Although it is conceivable that the H ϩ -coupled transporters can work in reverse for exporting sucrose from the phloem in "sink" tissues, direct evidence of this as the major export route is lacking (2,3). Perhaps more importantly, the microscopic distribution of sucrose within cellular compartments is largely unknown.…”
mentioning
confidence: 99%